2020
DOI: 10.1002/jcb.29677
|View full text |Cite
|
Sign up to set email alerts
|

PDK1 is important lipid kinase for RANKL‐induced osteoclast formation and function via the regulation of the Akt‐GSK3β‐NFATc1 signaling cascade

Abstract: Perturbations in the balanced process of osteoblast‐mediated bone formation and osteoclast‐mediated bone resorption leading to excessive osteoclast formation and/or activity is the cause of many pathological bone conditions such as osteoporosis. The osteoclast is the only cell in the body capable of resorbing and degrading the mineralized bone matrix. Osteoclast formation from monocytic precursors is governed by the actions of two key cytokines macrophage‐colony‐stimulating factor and receptor activator of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In particular, it has been shown that GSK3β suppresses the capacity of NFATc1 to bind to DNA, which hinders NFATc1-dependent gene transcription ( Neal and Clipstone, 2001 ). Furthermore, the latest research shows that a wide range of cytokines, guanine nucleotide binding protein subunit α13 (G α 13), 3-phosphoinositide-dependent protein kinase 1 (PDK1), and microtubule actin crosslinking factor 1 (MACF1) can manage osteoclastogenesis by regulating the Akt-GSK3β-NFATc1 signaling axis ( Wu et al, 2017a ; Lin et al, 2019 ; Xiao et al, 2020 ). Our results showed that asiatic acid inhibited Akt phosphorylation and activation of the NFATc1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that GSK3β suppresses the capacity of NFATc1 to bind to DNA, which hinders NFATc1-dependent gene transcription ( Neal and Clipstone, 2001 ). Furthermore, the latest research shows that a wide range of cytokines, guanine nucleotide binding protein subunit α13 (G α 13), 3-phosphoinositide-dependent protein kinase 1 (PDK1), and microtubule actin crosslinking factor 1 (MACF1) can manage osteoclastogenesis by regulating the Akt-GSK3β-NFATc1 signaling axis ( Wu et al, 2017a ; Lin et al, 2019 ; Xiao et al, 2020 ). Our results showed that asiatic acid inhibited Akt phosphorylation and activation of the NFATc1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…GSK3β-mediated phosphorylation of NFATc1 at serine residues promotes NFATc1 nuclear export and localization in the cytoplasm ( 33 , 34 ). RANKL stimulates the phosphorylation of GSK3β at serine 9, leading to its inactivation, the blockage of NFATc1 phosphorylation, and promotion of NFATc1 nuclear localization.…”
Section: Discussionmentioning
confidence: 99%
“…GSK3β-mediated phosphorylation of NFATc1 at serine residues promotes NFATc1 nuclear export and localization in the cytoplasm 21,31 . RANKL stimulates phosphorylation of GSK3β at serine 9 and inactivates GSK3β.…”
Section: Discussionmentioning
confidence: 99%